1969
DOI: 10.1113/jphysiol.1969.sp008848
|View full text |Cite
|
Sign up to set email alerts
|

The effect on drinking in the rat of intravenous infusion of angiotensin, given alone or in combination with other stimuli of thirst

Abstract: SUMMARY1. Intravenous infusion of angiotensin causes rats which are in water balance to drink water.2. The mean amount of angiotensin needed to initiate drinking was 291 + 4-6 jtg/kg (S.E. of mean) in twenty normal rats, and 15-7 + 241 ,g/kg in thirty-four nephrectomized rats.3. The nephrectomized rat is therefore more sensitive to this action of angiotensin than the rat with intact kidneys.4. The rates of infusion (0.05-3.0 jtg/kg-l min-) which cause drinking are comparable to those used to produce other effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
2

Year Published

1973
1973
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(80 citation statements)
references
References 13 publications
4
74
2
Order By: Relevance
“…Interestingly, both tissues which contain renin activity, the kidney and the submaxillary gland, are essential for thirst induced by hypovolemia (Gutman & Benzakein, 1969;Gutman et al, 1971) and the renin-angiotensin system has been demonstrated to be a thirst-inducing stimulus (Fitzsimons & Simons, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both tissues which contain renin activity, the kidney and the submaxillary gland, are essential for thirst induced by hypovolemia (Gutman & Benzakein, 1969;Gutman et al, 1971) and the renin-angiotensin system has been demonstrated to be a thirst-inducing stimulus (Fitzsimons & Simons, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Following the early demonstrations by Fitzsimons and colleagues that water drinking was a response to stimulation of the renin-angiotensin-aldosterone system 56 or to systematically-administered Ang II, 57 the question arose as to its site of action in the brain. How could a circulating peptide like Ang II, which is unable to cross the blood-brain barrier, induce water drinking?…”
Section: Thirstmentioning
confidence: 99%
“…In the next section, we examine data on angiotensin II (A-II). It is a known dipsogen in animals (Fitzsimons and Simons 1969), and in man, it is associated with dis orders with abnormal thirst (Yamamoto et al, 1986;Phillips et al 1985b). Dopamine-2 blockade by typical neuroleptics increases A-II-induced thirst in animals (Sumners et al 1981) and enhances peripheral response to A-II in man (Missale et a1.…”
Section: Classificationmentioning
confidence: 99%
“…Angiotensin II has a profound effect on thirst and drinking in animals. Angiotensin II injected intravenously (Fitzsimons and Simons 1969) and intraven· triculariy (Epstein et a1. 1970) causes a potent and im· mediate dipsogenic response.…”
Section: Thirst Physiology and Angiotensinsmentioning
confidence: 99%